Suboptimal Integration of Reward Magnitude and Prior Reward Likelihood in Categorical Decisions by Monkeys - Teichert, Tobias; Ferrera, Vincent P. (Frontiers in Neuroscience, 2010)
Sensory decisions may be influenced by non-sensory information regarding reward magnitude or reward likelihood. Given identical sensory information, it is more optimal to choose an option if it is a priori more likely to be correct and hence rewarded (prior reward likelihood bias), or if it yields a larger reward, given that it is the correct choice (reward magnitude bias). Here, we investigated the ability of macaque monkeys to integrate reward magnitude and prior reward likelihood information into a categorical decision about stimuli with high signal strength but variable decision uncertainty. In the asymmetric reward magnitude condition, monkeys over-adjusted their decision criterion such that they chose the highly rewarded alternative far more often than was optimal; in contrast, monkeys did not adjust their decision criterion in response to asymmetric reward likelihood. This finding shows that in this setting, monkeys did not adjust their decision criterion based on the product of reward likelihood and reward magnitude as has been reported to be the case in value based decisions that do not involve decision uncertainty due to stimulus categorization.